Synthesis and Characterization of New Benzothiazole-derived Schiff Bases Metal Complexes (Baghdad Science Journal, 2022)
Nitrogen-comprising heterocyclic compounds and their derivatives have empirically been invaluable as therapeutic agents. Fundamentally, 4-chloro-6-nitro-2-amino-1,3-benzothiazole 1 was synthesized via bromination of 2-chloro-4-nitro aniline with ammonium thiocyanate. This new heterocyclic haloorganoamino-1,3-benzothiazole derivative, was a starting material, which condensed and tethered with three different aromatic aldehyde pendant arm in presence of ethanol and glacial acetic acid isolating an interesting sequence of tridentate Schiff bases 2-4. These compounds were used for complexation reactions in 1:1 (metal: ligand) stoichiometry to obtain heteroleptic Al(III), Ni (II) and K(I) benzothiazole chelates 5-7(a-c) of the type [Al(L)Cl2, Ni(L)Cl, K(L) {L = Schiff base derivatives}]. The newly synthesized complexes were characterized by the melting points, IR and some of them by 1H-NMR spectroscopy and only one by X-ray techniques. The structures of complexes were anticipated from the spectroscopic studies.